DAYA TARIK WISATA TAMAN AERO SPORT SEBAGAI OBJEK WISATA KELUARGA DI KOTA PEKANBARU, PROVINSI RIAU - Bashiroh, Ainul; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Aero Sport Park, also known as Angkasa Pura Aircraft Park is one of the tourist attractions in Pekanbaru. The purpose of this research is to find out what tourist attractions are owned by the Aero Sport Park tourist attraction that can be enjoyed by visiting tourists based on the criteria of tourist attraction something to see, which is a tourist attraction that must have something that can be used as a spectacle by visitors. Something to do, is something that tourists can do to give a feeling of happiness. And something to buy, is a facility for tourists to shop. This research is qualitative research. Data collected through observation, documentation, and literature study. After the data is collected, the data is analyzed descriptively qualitatively and presented in the form of a report. The results showed that Aero Sport Park fulfills the criteria of the tourist attraction something to see, the audience can see the fuselage, observe the crowd, watch the event, and see the sunset by the lake. Something to do, visitors can color, play bicycles and electric motorbikes, play in the playground, feed rabbits, and ride carousels. And something to buy, visitors can buy local to oriental food. Keywords: Aero Sport Park, Tourism Attraction, something to see, something to do, something to buy.